Labelling of Bleomycin with Cobalt-57, Indium-111, Technetium-99m, Mercury-197, Lead-203, and Copper-67 - van de Poll, M. A. P. C; Versluis, A.; Rasker, J. J.; Jurjens, H.; Woldring, M. G. (Nuklearmedizin - NuclearMedicine, 1976)
The radiochemical purity of the cobalt-57 complex of bleomycin could be enhanced by adjusting the pH of the final product to a value between 5 and 6. This radiopharmaceutical appeared to have better tumor visualizing properties compared to the not neutralized preparation.The clinical use of the cobalt-57 bleomycin complex is however limited by the long physical half-life of the label, causing a risk of radioactive contamination. It appeared to be possible to label bleomycin with radioactive cations (111In3+, 99mTc4+, 197Hg2+ and 67Cu2+) having suitable gamma ray energies and short half-lifes.These bleomycin complexes showed a high radiochemical purity judged by their behaviour on thin layer chromatography, paper chromatography, and electrophoresis, but their application as tumor visualizing radiopharmaceutical turned out to be disappointing compared with cobalt-57 bleomycin.